A comprehensive spatiotemporal map of dystrophin isoform expression in the developing and adult human brain - Francesco Catapano; Reem Alkharji; Darren Chambers; Simran Singh; Artadokht Aghaeipour; Jyoti Malhotra; Patrizia Ferretti; Rahul Phadke; Francesco Muntoni (Acta Neuropathologica Communications)
Abstract Mutations in the dystrophin gene (DMD) cause the severe muscle-wasting disease Duchenne muscular dystrophy (DMD). Additionally, there is a high incidence of intellectual disability and neurobehavioural comorbidities in individuals with DMD. Similar behavioural abnormalities are found in mdx dystrophic mouse models. Unlike muscle, several dystrophin isoforms are expressed in the human brain, but a detailed map of regional and cellular localisation of dystrophin isoforms is missing. This is crucial in understanding the neuropathology of DMD individuals, and for evaluating the translatability of pre-clinical findings in DMD mouse models receiving genetic therapy interventions. Here, we provide a comprehensive dystrophin expression profile in human brains from early development to adulthood. We reveal expression of dp427p2, dp427c, dp427m and dp40 isoforms in human embryonic brains, not previously reported. We also detected dp427p2 expression and developmental regulation in human brain across the lifespan. In addition we showed by in situ hybridisation that dp140 was greatly downregulated in adult brains. Importantly, our data also demonstrate expression of DMD transcripts in human motor neurons and co-expression of different dystrophin isoforms within single neurons in both developing and adult brains. Finally, we show localisation of DMD transcripts with GAD1+ GABAergic-associated transcripts in neurons including cerebellar Purkinje cells and interneurons, as well as in the majority of neocortical and hippocampal SLC17A7+ glutamatergic neurons, suggesting a role for dystrophin in signalling at the neuronal inhibitory and excitatory synapses. Graphical abstract